The Government's Role as a Pioneer in Raising Public Awareness About Waste Management: Peran Pemerintah Sebagai Pelopor dalam Meningkatkan Kesadaran Masyarakat Tentang Pengelolaan Sampah - Anggraeni, Risa Prasasti; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2020)
The role of the village government in this case is influential in increasing public awareness about waste management in Lalak Village with the village government program, namely sorting waste independently which aims to increase public awareness about the importance of waste management due to the lack of role of the village government in increasing public awareness through management rubbish. The purpose of this study was to determine and understand the role of the village government which has an impact on public awareness in waste management in Lajuk Village, Porong District, Sidoarjo Regency. This study focuses on the role of the village government, namely the role of the village government as a pioneer. The method used in this study is descriptive qualitative method with data collection techniques carried out by observation, documentation, interviews with informants and using sources from books and journals.